THE RELATIONSHIP BETWEEN FEAR, OBSESSION AND QUALITY OF LIFE IN CHRONIC PATIENTS DUE TO COVID-19 PANDEMIC - Ozer, Ziilfiinaz; Turan, Giilcan Bahcecioglu; Teki, Neslihan (Medicinska Naklada Zagreb, 2022)
Aim: Excessive fear and repetitive negative thoughts about COVID-19 in individuals with chronic diseases, who are among high risk group in COVID-19 pandemic may cause psychological disorders such as obsession and affect the quality of life negatively. This study was conducted to examine the relationship betweenfear, obsessive behaviors and quality of life in chronic patients due to COVID-19 pandemic. Subjects and methods: This descriptive and cross-sectional study was carried out between October 5 and 31, 2020. The survey form was sent online to individuals with a chronic disease who were 18 and older. 255 individuals who responded to surveys were included in the study. The data were collected with Personal Information Form, Fear of COVJD-19 Scale (FCV-19S), Obsession with COVID-19 Scale (OCS) and World Health Organization Quality of Life BriefForm (WHOQOL-BREF-TR). Results: Fear of COVID-19 Scale mean score wasfound as 21.99±7.28, OCS mean score was found as 4.78±3.62, WHOQOL-BREF-TR physical subdomain mean score was found as 13.58±3.35, psychological subdomain mean score was found as 14.19±3.29, social subdomain mean score was found as 14.13±3.66, environmental subdomain mean score was found as 14.16±3.36, and national environmental subdomain mean score was found as 13.83±2.82.A positive and moderate significant correlation was found between FCV-19S and OCS (r=0.571, p=0.000). A positive and very weak significant correlation was found between OCS and WHOQOL-BREF-TR physical subdomain (r=0.166, p=0.00). Conclusion: The participants were found to have high levels of fear of COVID-19 and low levels of obsession with COVID-19. It wasfound that individuals'fears increased obsessive thoughts and obsessive thoughts positively affected quality of life. © 2022 Medicinska Naklada Zagreb. All rights reserved.
Keywords: Chronic Disease; COVID-19; Fear; Obsession; Quality of Life